Psicología Comunitaria, Programas Sociales y Neoliberalismo: La Experiencia Chilena - Winkler-Muller, M (Sociedad Interamericana de Psicologia, 2019)
The value antagonism between Community Psychology (PC) and Neoliberalism conditions professional work. In order to know the way in which the tension between neoliberal policies and community psychology unfolds, the ways in which the community perspective is integrated into a set of government programs in Chile, which are declared "community", are described and analyzed. The results show that the public policy programs reviewed, do not meet the possibilities of the PC to strengthen communities. There is an urgent need to recover and strengthen the consideration of the ethical-political dimension in professional training and the participation of the PC in public policies. © 2019, Sociedad Interamericana de Psicologia. All rights reserved.